Perturbation Treadmill Training in Parkinson's Disease A Novel Approach for Neurological Rehabilitation - Klamroth, Sarah (Best of Therapie,, 2018)
Sarah Klamroth describes a novel treadmill training device, which applies additional perturbations to the walking surface and thereby simulating an uneven surface. In a pilot study the author investigated the immediate effects on gait and postural control in patients with Parkinson's Disease after a single training session of perturbation treadmill training. The results show that perturbation treadmill training is feasible for mildly to moderately affected Parkinson patients, and that one training session led to improvements in overground walking speed and gait variability in these patients. Contents Devices for Perturbation Treadmill Training Motor Adaptations Gait and Postural Control in Parkinson's Disease Target Groups Scientists and students in the field of physical therapy, sport science, and neurology Practitioners in the field of physical therapy, sport science, neurology, and rehabilitation About the Author Sarah Klamroth is Physical Therapist and Sport Scientist, and currently she does her PhD with a focus on Physical Activity and Quality of Life in Parkinson's Disease at the Department of Sport Science and Sport (Division of Exercise and Health, Prof. Dr. Klaus Pfeifer) of the Friedrich-Alexander-University Erlangen-Nuremberg.